The Influence of Autonomous Motivation and Professional Competence on the Performance of Al-Qur’an Hadith Teachers through Self-Efficacy - Muhammad Latif Nawawi; Fajri Ismail; Choirun Niswah; Indah Wigati; Maryamah; Hartatiana (Yayasan Darusssalam Bengkulu, 2026)
This study examines the influence of autonomous motivation and professional competence on the performance of Al-Qur’an Hadith teachers through the mediating role of self-efficacy in Madrasah Tsanawiyah (Islamic Junior High Schools) across Central Lampung Regency, Indonesia. The study addresses the limited integrative research combining motivational, professional, and psychological factors in explaining teacher performance within the context of Islamic education, particularly among Al-Qur’an Hadith teachers who carry pedagogical, moral, and spiritual responsibilities. Using a quantitative survey design conducted from June 2025 to April 2026, the study involved 98 certified Al-Qur’an Hadith teachers selected through total sampling techniques. Data were collected through validated Likert-scale questionnaires distributed online via Google Forms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that autonomous motivation and professional competence significantly improve teacher performance both directly and indirectly through self-efficacy. Self-efficacy significantly mediated the relationship between autonomous motivation and teacher performance (β = 0.308; T = 2.549; p = 0.011), indicating that teachers with stronger intrinsic motivation and greater confidence in their teaching abilities demonstrate higher professional performance, adaptability, and commitment in instructional practices. Conversely, controlled motivation did not significantly influence teacher performance through self-efficacy (β = 0.008; T = 0.106; p = 0.916). This study contributes an integrative empirical model linking motivational quality, professional competence, and efficacy beliefs in improving teacher performance within Islamic education contexts.